Towards An Entrepreneurship And Stem Education Primary School Curriculum In Zimbabwe: A Case Study Of Bumburwi Of Gweru District. - Saiden, Thondhlana (Advances in Social Sciences Research Journal, 2017)
The study sought to establish the setting up of an entrepreneurial skills base in Zimbabwe ‘s new education curriculum and how this new curriculum relates to STEM concept. Related literature exhibited that entrepreneurship skill development at early stages of learning contribute immensely to economic development of a country. These research findings appear to answer Zimbabwe’s economic challenges hence the need to check on the existence of entrepreneurship skills in the new curriculum. Both qualitative and simple descriptive statistics approaches were used to analyse data. The research revealed that there are entrepreneurship skills inherent in the new curriculum that do need advancement. The curriculum implementers were not ready in any way as they lacked the basic skills in entrepreneurship development. It was recommended that; the curriculum development unit include the areas on entrepreneurship left out and that entrepreneurship was to be linked with STEM aspects to spearhead economic development.